2018
DOI: 10.1159/000489988
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27b Impairs Adipocyte Differentiation of Human Adipose Tissue-Derived Mesenchymal Stem Cells by Targeting LPL

Abstract: Background/Aims: In this study, the molecular mechanisms of miR-27b and lipoprotein lipase (LPL) that regulate human adipose-derived mesenchymal stem cells (hASCs) adipogenic differentiation were detected. Methods: Microarray analysis was applied to screen for differentially expressed miRNAs and mRNA during hASCs adipocyte differentiation induction. MiR-27b and LPL were found to have abnormal expression. Then, a dual luciferase reporter assay was employed to validate the targeting relationship between miR-27b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…One of the miR-30 target is the RUNX2 (osteogenesis transcription factor) which could be, at least in part, responsible for miR-30 positive effects on adipocyte differentiation ( Zaragosi et al, 2011 ). Another study using microarray analysis found 32 miRNAs differentially expressed during adipogenesis, among them is miR27b which was downregulated, while lipoprotein lipase (LPL) mRNA was up-regulated ( Hu et al, 2018 ). miR-27b targeted LPL and inhibits adipogenic differentiation ( Hu et al, 2018 ).…”
Section: Gene Expression Profile In Adipogenesis Of Mscmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the miR-30 target is the RUNX2 (osteogenesis transcription factor) which could be, at least in part, responsible for miR-30 positive effects on adipocyte differentiation ( Zaragosi et al, 2011 ). Another study using microarray analysis found 32 miRNAs differentially expressed during adipogenesis, among them is miR27b which was downregulated, while lipoprotein lipase (LPL) mRNA was up-regulated ( Hu et al, 2018 ). miR-27b targeted LPL and inhibits adipogenic differentiation ( Hu et al, 2018 ).…”
Section: Gene Expression Profile In Adipogenesis Of Mscmentioning
confidence: 99%
“…For differentiation induction, several protocols have been established to promote adipogenesis, chondrogenesis and osteogenesis which includes the usage of different culture media ( Table 1 ), passage number and confluency. In the manuscripts analyzed in this review, the passage at which differentiation was induced ranged from 2-3 ( Kulterer et al, 2007 ; Gu et al, 2017 ; Huang et al, 2017 ; Hu et al, 2018 ; Shaik et al, 2019 ) to 15 ( Ambele et al, 2016 ). Regarding confluency, some groups reported that the differentiation was induced with subconfluent cells (up to 90% confluence) ( Hu et al, 2018 ; Yi et al, 2019 ), others used confluent cultures ( Zaragosi et al, 2011 ; Luan et al, 2015 ; Xu et al, 2016 ; Min et al, 2019 ), or even a few days after the cells reached confluence ( Scheideler et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPL and C/EBPα have important roles in preadipocyte differentiation and cellular lipid accumulation. The expression of these two genes begins with lipogenesis and induces lipoprotein storage and lipid metabolism (Bauer et al, 2015;Rozovski et al, 2016;Glatz and Luiken, 2017;Hu et al, 2018). Consistent with this, the expression of PSMA1 is potentially associated with LXRα, which is the upstream regulator of LPL and C/EBPα (Zhang et al, 2001;Steffensen et al, 2002;Kim et al, 2007b;Han et al, 2009).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have indicated that miR-27b plays an important role in lipid metabolism and adipogenesis [24,25]. It has been reported that miR-27b is down-regulated in in vitro cultured adipocytes and adipose tissue in obesity-related models and that miR-27b impairs adipocyte differentiation in 3T3-L1 cells and human adipose-derived mesenchymal stem cells via its associations with PPARγ and C/EBPα [24][25][26][27]. In zebrafish, depletion of miR-27b has shown increases in PPARγ, C/EBPα, and SREBP-1c, resulting in the enhancement of adipocyte hyperplasia [28].…”
Section: Discussionmentioning
confidence: 99%